2012
DOI: 10.1039/c2cc34168a
|View full text |Cite
|
Sign up to set email alerts
|

An ICT-based ratiometric probe for hydrazine and its application in live cells

Abstract: Hydrazine is an important industrial chemical but also very toxic thus requiring rapid detection agents. A ratiometric fluorescence probe that enables rapid, low-limit and naked-eye detection is successfully designed and used for hydrazine determination in live cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(83 citation statements)
references
References 24 publications
0
83
0
Order By: Relevance
“…However, to date, only a few papers are concerned with fluorescence methods for detection of N 2 H 4 . [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Many recognizing moiety of fluorescence sensors for N 2 H 4 have been developed, mainly including acetyl, [23][24][25][26] 4-bromo butyrate, [27][28][29] levulinate, 30,31 phthalimide, [32][33][34] aldehyde, 35 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: Introductionmentioning
confidence: 99%
“…However, to date, only a few papers are concerned with fluorescence methods for detection of N 2 H 4 . [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Many recognizing moiety of fluorescence sensors for N 2 H 4 have been developed, mainly including acetyl, [23][24][25][26] 4-bromo butyrate, [27][28][29] levulinate, 30,31 phthalimide, [32][33][34] aldehyde, 35 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, Tong et al reported that arylaldehydes react with hydrazine to produce a uorescent product.…”
Section: Introductionmentioning
confidence: 99%
“…Among these analytical approaches, spectrofluorimetry is standing out for its excellent sensitivity, high selectivity, noninvasiveness, and good compatibility for biosamples. Recent years, a lot of hydrazine detectors appeared [12][13][14][15][16][17][18][19][20][21][22][23][24]. All these works show that the research in the detection of hydrazine is of positive significance.…”
Section: Introductionmentioning
confidence: 99%
“…its large π-conjugate system, and easy to synthesize its derivatives [13,[35][36][37][38][39][40]. Therefore, we focused on coumarin as the fundamental platform for the design of the hydrazine fluorescence probe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation